Facilitation Effects of Acidic Chlorinated Salts on Reservoir Unblocking During In Situ Conversion of Huadian Oil Shale - Shaotao Xu; Liang Xu; Senhao Wang; Hanxi Wang; Sunhua Deng; Han Wang (Applied Sciences)
In order to explore the potential catalysts for kerogen pyrolysis and to clear away obstacles to product liberation in product recovery, the facilitation effects of acidic chlorinated salts (MnCl2·4H2O, AlCl3·6H2O, CrCl3·6H2O, and MoCl5) on pyrolysis behavior of Huadian oil shale (OS) were investigated. Two different ways of wet mixing and dry mixing were used, and indoor pyrolysis experiments were carried out to characterize the different products collected by multiple analyses. The acidic chloride solution could effectively remove large amounts of calcite from OS during wet mixing, whereas the calcite in the dry-mixed samples decomposed significantly during pyrolysis, releasing significant amounts of CO2. AlCl3 could improve the pore space by removing carbonates, which can promote the pyrolysis of kerogen and increase oil yield. The improved pore space can also promote the conversion of kerogen and the release of hydrocarbon products, while the large amounts of CO2 released during pyrolysis of dry-mixed samples can promote the migration of heavy fractions. This study emphasizes the great potential of acid chlorates in counteracting reservoir blockage and facilitating pyrolysis for OS in situ exploitation.